PARSEME.1st : SGML for software developers - McGrath, Sean (The Charles F. Goldfarb series on open information management, 1998)
PARSEME.1ST is the first developer's guide to both SGML's practicalities and its worldview. It will tell you everything you need to build world-class SGML systems and products. Start by walking through all the basics of SGML - from the perspective of an experienced developer. Understand the structure of SGML documents and systems - and how SGML can solve a remarkable number of real-world problems. Then, get the detailed information and worked examples you need to implement practical solutions.